ASPEK PENALARAN DALAM PENGAJARAN BAHASA INDONESIA - Dailami Dailami (Ta'dib, 2011)
The ability to use correct and appropriate language is the main requirement to carry out scientific activities since language is the fundamental scientific tool for communication. Communicative aspects should arrive at the highest level of the expected scientific communication. Furthermore, scientific works should not be limited to those of using popular language, i.e. sentence structures and terminologies, especially in communication among scientist. Understanding language aspects and terminologies of foreign language help language reasoning, both in terms of basic and derivational forms. Singular forms are more advisable except if the context tends to be plural. The choice of forms depends upon 1) situational context and sentence bound, 2) easiness in language learning, and 3) practicality.Kata kunci: aspek penalaran, pengajaran, bahasa Indonesia